On matrix operators on the series space |N_p^θ|_k - Mohapatra, R. N.; Sarigol, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Recently, the space |N_p^θ|_k has been generated from the set of k-absolutely convergent series _k as the set of series summable by the absolute weighted method. In the paper, we investigate some properties of this space, such as β -duality and the relationship with k and then show that each element in the classes (|N_p|, |N_p^θ|_k) and (|N_p^θ|_k, |N_q|) of infinite matrices corresponds to a continuous linear operator and also characterizes these classes. Hence, in the special case, we deduce some well-known results of Sarıg¨ol, Bosanquet, Orhan, and Sunouchi.